Книгозбірня гетьмана Кирила Розумовського: наукове дослідження та реконструкція - Олійник, А.В. (Сіверщина в історії України, 2022)
У статті досліджено історію формування, тематичні напрями та подальшу долю приватного книжкового зібрання українського гетьмана Кирила Розумовського. The history of formation, thematic directions and further destiny of the private book collection of the Ukrainian hetman Kyrylo Rozumovskyi are investigated in the article. Four directions of research of the private library of the hetman are opened. The work of the staff of the National Reserve «Hetman’s Capital» on the reconstruction of the book collection of Kyrylo Rozumovskyi is analyzed.